OpenStudy (anonymous):

If you were to use the elimination method to solve the following system, choose the new system of equations that would result after the variable z is eliminated in the first and second equations, then the second and third equations. 3x - 7y - z = -14 3x + 3y + 2z = 1 2x + 5y - 2z = -16 A)3x - 7y = -14 2x + 5y = -16 B)9x - 11y = -27 5x + 8y = -15 C)9x - 11y = -27 3x - 7y = -14 D)2x + 5y = -16 5x + 8y = -15

3 years ago
OpenStudy (anonymous):

B

3 years ago
OpenStudy (mathstudent55):

For the first two eqs, multiply the first one by 2 and add them. For the last two eqs., just add them. What do you get?

3 years ago
Similar Questions: